PENGARUH KEPAMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA GURU SD NEGERI - Yuliawati, Yuliawati; Rini, Riswanti; Hariri, Hasan; Handoko, Handoko (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This research investigates how the leadership style of school principals, teacher commitment, and the organizational culture affect teacher discipline in Public Elementary Schools in the Banyumas District, Pringsewu Regency. The study uses a quantitative approach and includes 122 public elementary school teachers as participants. Data was collected through questionnaires, and analysis involved regression tests to assess normality, heteroskedasticity, multicollinearity, and data linearity. The findings show that both transformational leadership of the school principal and organizational culture have a positive and significant impact on teacher discipline. Moreover, when combined, these factors also positively and significantly influence teacher discipline.